MODEL KOLABORATIF PENCEGAHAN KEKERASAN BERBASIS PERMENDIKBUDRISTEK NO. 46 TAHUN 2023: PENDEKATAN AKSI-PARTISIPATIF - Gunawan Widjaja; Wagiman Martedjo; Ignatius Bambang Sukarno Hatta (Collegium Studiosum Journal, 2025)
This article aims to analyze the implementation gaps of the Ministry of Education Regulation No. 46 of 2023 on the Prevention and Handling of Violence in Educational Institutions and to propose a collaborative model based on participatory action as an alternative solution. Using a descriptive qualitative method and normative legal approach, this study explores principles of education law, community participation, and the institutional effectiveness of schools in violence prevention. Findings reveal that the regulation’s implementation still faces structural and cultural challenges, including low regulatory literacy among educators and limited stakeholder engagement. The proposed collaborative model emphasizes stakeholder synergy through tiered training, participatory dialogue forums, strategic partnerships, and community-based evaluation. It is expected to contribute to the creation of a safe, inclusive, and just learning environment.